Implementation of a Solar Cell-Based Power Supply System to Support the Operation of Boundary Marker Monitoring Devices: Telekomunikasi Militer - Yosera Rico Fahmi; Muhammad Ridwan; Ananda Herdi Akbar (Pustaka Poltekad, 2026)
Boundary markers in areas are like signs that show where the borders are and these borders need to be checked all the time for security. The big problem with using Internet of Things markers is that they need power all the time and this power has to come from a source that will not stop. Internet of Things boundary markers need a lot of power to work properly. This research is, about making a system that uses energy from the sun to power Internet of Things boundary markers. Internet of Things boundary markers will use cells to get the power they need. The system has panels that give us 20 to 50 watts of power. It also has a controller to charge the battery and a 12 volt lithium battery to store the power. There is a computer called an IoT module, which is an ESP32, that checks where the boundary marker is and sends this information to the server.